2015
DOI: 10.1590/0103-8478cr20141711
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of ochratoxin A in grapes, juices and wines and risk assessment related to this mycotoxin exposure

Abstract: Ochratoxin A (OTA) is a mycotoxin with nephrotoxic, genotoxic, teratogenic and carcinogenic properties. The presence of this toxin in wines and juices occurs due to the development of toxigenic fungi in grapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…It has been shown that 7% of Aspergillus niger isolates from herbal teas are able to produce OTA . Aspergillus niger and A. carbonarius should be highlighted both for their high incidence and for their great capacity to produce OTA …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that 7% of Aspergillus niger isolates from herbal teas are able to produce OTA . Aspergillus niger and A. carbonarius should be highlighted both for their high incidence and for their great capacity to produce OTA …”
Section: Introductionmentioning
confidence: 99%
“…The predominant OTA producing fungi in grapes are from the genus Aspergillus (Dachery, Manfroi, Berleze, & Welke, 2016;Leong, Hocking, & Scott, 2006a;Leong, Hocking, & Scott, 2006b;Rousseaux, Diguta, Radoï-Matei, Alexandre, & Guilloux-Bénatier, 2014) (Table 1) and particularly A. carbonarius and A. niger (Frisvad et al, 2007). Samson et al (2014) demonstrated that A. tubingensis and A. niger/ welwitschiae clades each contain strains of high similarity, but the clades are well separated from each other as determined by the calmodulin sequences.…”
Section: Ochratoxin a And Producing Fungi From Grapesmentioning
confidence: 99%
“…OTA is a mycotoxin produced mainly by fungi of the genera Aspergillus and Penicillium under particular environmental conditions. Recent studies have demonstrated that OTA is frequently present in a series of beverages, particularly green coffee [21][22][23], beer [24,25] and wine [26][27][28][29]. This mycotoxin is nephrotoxic, hepatotoxic, genotoxic, teratogenic and immunotoxic to animals and its carcinogenicity in rats and male mice is well-established [30,31].…”
Section: Biosensors For the Detection Of Ochratoxin A In Wine Beer Amentioning
confidence: 99%